QUR’AN AND SCIENCE: A STUDY OF THE COMPATIBILITY OF QUR’ANIC VERSES WITH MODERN SCIENTIFIC THEORIES - Ashiq Hussain Mir (Fakultas Agama Islam Universitas Wiralodra, 2019)
Qur’an is the infallible Word of God and since its inception in the world of Space and Time its immutability has been proven time and again. In all the fields of Knowledge it proved to be a miracle of the Divine. Its literary quality is unparalleled and its teachings are the ultimate remedy for the ailments of mankind. Though it’s not a book of empirical sciences, we still can find much compatibility of its contents with the modern established scientific theories. Some verses of the Qur’an are much similar to the observational theories of cosmology and biology that the likeness deems it impossible to be a work of any man of the 7th century. In this paper I have tried to compare some Qur’anic verses with some of the important theories of modern Cosmology like the Big Bang theory and expansion of the Universe. I have also brought the modern observational knowledge of embryology as being compatible with many verses dealing with same subject of the evolution of embryo into fetus and the stages of a baby inside a mother’s womb. Qur’an is a fascinating book which at the one hand satisfies the spiritual quest of the mystically inclined and on the other hand gives rational satisfaction to a scientifically minded rationalist. It is for a common layman and for a philosopher as well. It is the guideline for the social, economic and political endeavors of man and a complete religious treatise as well. We can rightly assume that the precise scientific hints in the Holy Qur’an is a part of much studies ‘Ijaz ul Qur’an and there is no harm in making science as a tool in presenting and sharing Islam with Humanity. It is a part of argumentative polemics and a defense of Faith and many scholars use this methodology in Da’wah work all over the world. It is also important because scientific method is the most dominant method in the present world and this method can be used to combat the philosophical materialism and atheistic ideologies.